2014
DOI: 10.1292/jvms.14-0158
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Avian Influenza Virus, Newcastle Disease Virus and Goose Parvovirus Using Solution of Nano-Sized Scallop Shell Powder

Abstract: Scallop shell powder produced by calcination process − the average diameter of the powder particles being 20 µm (SSP) − was further ground into nano-sized particles, with average diameter of 500 nm, here designated CaO-Nano. Solution of CaO-Nano could inactivate avian influenza virus within 5 sec, whereas the solution of SSP could not even after 1 hr incubation. CaO-Nano solution could also inactivate Newcastle disease virus and goose parvovirus within 5 sec and 30 sec, respectively. The virus-inactivating cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…Scallop shell powder ground to nanometer range showed exceptional inactivation property against avian influenza virus (also Newcastle disease virus and goose parvovirus) within 5 seconds of incubation. The study [103] showed that calcium oxide, which does not show any activity at 2 µm size, elicit inhibitory behavior at 550 nm size. In another study [104], the ability of vaccines to induce a T-cell response was mimicked by calcium phosphate nanoparticles.…”
Section: 3 Studies On Influenza Virusmentioning
confidence: 99%
“…Scallop shell powder ground to nanometer range showed exceptional inactivation property against avian influenza virus (also Newcastle disease virus and goose parvovirus) within 5 seconds of incubation. The study [103] showed that calcium oxide, which does not show any activity at 2 µm size, elicit inhibitory behavior at 550 nm size. In another study [104], the ability of vaccines to induce a T-cell response was mimicked by calcium phosphate nanoparticles.…”
Section: 3 Studies On Influenza Virusmentioning
confidence: 99%
“…Inactivation was considered to be satisfied when RF was ≥3 (Alphin et al, 2009;Hasegawa et al, 2013;Lombardi et al, 2008;Takehara et al, 2009;Thammakarn et al, 2014).…”
Section: − (Amount Of Treated Virus With Bcx/ml)]mentioning
confidence: 99%
“…Separation of two layers due to flocculation/precipitation was observed in all samples, except under acidic conditions. The TC and CF cell counts in supernatants of the BiSCaO and BiSCa(OH) 2 colloidal dispersions at pH ≥ 11 were much lower compared with samples at other pH values (pH ≤ 10), and the antimicrobial effect was more pronounced with BiSCaO colloidal dispersions than with BiSCa(OH) 2 colloidal dispersions at each pH (pH [5][6][7][8][9][10][11][12]. No TC and CF were observed following treatment with BiSCaO colloidal dispersion at pH 12 ( Figure 5).…”
Section: Antimicrobial Efficacy Of Biscao and Bisca(oh) 2 Colloidal Dmentioning
confidence: 97%
“…The main component of scallop shells is calcium carbonate (CaCO 3 ), which is converted to CaO when heated at over 800 • C. Heated scallop shell powder is composed mainly of CaO, which we called bioshell calcium oxide (BiSCaO), a material well known to exhibit strong antimicrobial activity [4]. For example, BiSCaO shows broad antimicrobial action against the avian influenza virus [5], bacteria [3,4], heat-resistant bacterial spores [3,6], fungi [7], and biofilms [8][9][10]. In addition, BiSCaO is used as an additive to prolong the shelf life of food products [10].…”
Section: Introductionmentioning
confidence: 99%